Targeting estrogen signaling and biosynthesis for aged skin repair - Zomer, Helena D.; Cooke, Paul S. (Frontiers in Physiology, 2023)
Non-healing skin wounds are disproportionally prevalent in older adults. Current treatments do not account for the particularities of aged skin and result in inadequate outcomes. Overall, healing chronic wounds in the elderly remains a major unmet clinical need. Estrogens play a critical role in reproduction but also have important actions in non-reproductive organs. Estrogen biosynthesis and signaling pathways are locally activated during physiological wound healing, processes that are inhibited in elderly estrogen-deprived skin. Estrogen deprivation has been shown to be a critical mediator of impaired wound healing in both postmenopausal women and aged men, and topical estrogen application reverses age-associated delayed wound healing in both elderly men and women. These data indicate that adequate estrogen biosynthesis and properly regulated estrogen signaling pathways are essential for normal wound healing and can be targeted to optimize tissue repair in the elderly. However, due to fundamental questions regarding how to safely restore estrogen signaling locally in skin wounds, there are currently no therapeutic strategies addressing estrogen deficiency in elderly chronic wounds. This review discusses established and recent literature in this area and proposes the hypothesis that estrogen plays a pleiotropic role in skin aging and that targeting estrogen signaling and biosynthesis could promote skin repair in older adults.